GAMBARAN KEJADIAN PENYAKIT SCABIES DI PONPES AL ITQON DI PATEBON KENDAL - Rini Megawati; Budi Santosa; Didik Sumanto (JURNAL LITBANG, 2005)
Abstract Scabies disease in Indonesia is commonly called scabies skin disease, caused by Sarcoptes scabiei mite, it is infected by personal hygiene and bad environment, the most effective way to Decrease the infection spreading of scabies disease is cleaning the environmental and Surrounding frequently and keep the personal hygiene. In this research place with many people live in is chosen, like Pondok Pesantren, because Usually there are many people in Pondok Pesantren and they less pay attention on keeping the Personal and environmental hygiene, and also the facility provided by Ponpes organizer is not enough. The purpose of this research is to do observation the scabies disease and to low personal hygiene related to scabies disease. The used research is descriptive research because it just describes scabies disease at boys and girls students in Pondok Pesantren Al ltqon. The used research Method to examine skin rabbed with a coin is by Microscopic method. Population is boys and girls student at Pondok Pesantren At ltqon amount to I15 children, Sample is boys and girls students having scabies disease symptom amount to 15 samples in Pondok Pesantren. Result of research shows that respondent infected by Sarcoptes scabiei there is 27 % while the result of interview to know hygiene and sanitation habit got the data that 54 % respondent Have bad habit. Keyword: scabies